CoQ10 and L-Carnitine Attenuate the Effect of High LDL and Oxidized LDL on Spermatogenesis in Male Rats - Ghanbarzadeh, S.; Garjani, A.; Ziaee, M.; Khorrami, A. (Drug Research, 2014)
It is estimated that one-third of infertility cases are due to male factors. Hypercholesterolemia is a social problem in many developed countries and contributed with a heterogeneous group of disorders characterized by an excess of cholesterol and its derivatives in the blood stream.The objective of the present study was to investigate the protective effects of coenzyme Q10 and L-Carnitine supplementation on semen parameters, sperm function and reproductive hormone profiles in male Wistar rats with high LDL and Oxidized LDL (OxLDL) blood levels.Animals were fed with cholesterol and oxidized cholesterol-rich diets for 14 weeks to elevate the LDL and OxLDL blood level, respectively. Pretreatment with coenzyme Q10 (10 mg/kg/day, oral) and L-Carnitine (350 mg/kg/day, oral) were conducted for 5 consecutive weeks. Sex hormones levels, malondialdehyde and total antioxidant concentrations, as well as testis, epididymis and seminal vesicle weight were also analyzed.Following high LDL and OxLDL blood levels, decrease in the sperms count and viability, weights of testis, epididymis and seminal vesicle as well as concentration of testosterone and LH hormone were observed. On the other hand, in contrast to reduction of total antioxidant level, malondialdehyde concentration, both in serum and testis, was increased. However, pretreatment with L-carnitine and coenzyme Q10 increased serum sex hormones level and improved semen parameters significantly.Overall, pretreatment with coenzyme Q10 and L-Carnitine attenuated the destructive effects of high LDL and oxidized LDL levels on spermatogenesis parameters in male rats.
Keywords: LDL; oxidized LDL; spermatogenesis; L-carnitine; coenzyme Q10